SPBE Policy Evaluation in Army Physical Services Toward One Physical Data Service - R. Aris Sumowijoyo; Muhamad Nur Afandi; Sait Abdullah; Hendrikus T Gedeona (Goodwood Publishing, 2026)
Purpose: This study aims to evaluate the implementation of the Electronic-Based Government System (SPBE) within the Indonesian Army’s Physical Services Department (Dinas Jasmani Angkatan Darat od Disjasad), focusing on the Physical Information System (Sisfojas) as a digital service innovation for managing single physical data. The evaluation seeks to identify challenges and formulate strategies to improve the system’s effectiveness, efficiency, and integration. Methodology: This study uses a descriptive qualitative approach based on William N. Dunn’s policy evaluation model, which includes six dimensions: effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. Data were collected through interviews, observations, and document reviews, and analyzed using Miles and Huberman’s interactive model with triangulation. Results: The findings indicate that Sisfojas has not been optimally implemented as an evidence-based decision-making tool. The limitations include low data update frequency, uneven participation among units, and lack of regulatory reinforcement. Despite its potential to support leadership decisions and data integration, current SPBE practices remain centralized within a single unit (Infolahta) and lack comprehensive coordination. Conclusions: Improving SPBE implementation requires six key actions: regulatory updates, human resource capacity building, system modernization, role restructuring, hybrid work integration, and performance incentives linked to SPBE data, summarized in a logical framework for sustainable improvement. Limitations: The study is limited to Sisfojas in Disjasad and does not cover other military branches or broader populations. Contributions: This study contributes theoretically by adapting Dunn’s evaluation model to military digital governance and practically by proposing a policy roadmap for improving SPBE through regulatory, cultural, and technological reforms.